MAKNA PERTUNJUKAN DABUIH PADA MASYARAKAT LUMPO PESISIR SELATAN SUMATERA BARAT - Yuniarti Munaf (Imaji, 2007)
The aims of this study are to know the functions of Dabuih performance in Lumpo of Pesisir Selatan Regency and its meanings. The analysis of meaning is focused on the supporting aspects, including stage and spectators. It is a qualitative research adopting an interaction symbolism. The informants, selected through the snowball sampling technique, were the village chief, Dabuih players, influential villagers, and spectators. The data were analyzed by using Spradley analysis model (1997). The validity was based on their credibility, transferability, dependability and conformability. The findings show that 1) Dabuih traditional art performance still exists and is preserved by Lumpo people. In its earlier development, Dabuih was a medium to introduce the Islamic teachings, but in the later development it was used as entertainment; 2) the meanings of Dabuih are related to religious and traditional aspects of the local people. To Dabuih viewers, the performance is religiously educative, integrative and entertaining media. Key Words: the meanings of Dabuih, a performance in Lumpo